Reproduction in Animal Models of Lysosomal Storage Diseases: A Scoping Review - Vuolo, Daniela; Do Nascimento, Cinthia Castro; D’Almeida, Vânia (Frontiers in Molecular Biosciences, 2021)
Background: Lysosomal storage diseases (LSDs) are caused by a mutation in a specific gene. Enzymatic dysfunction results in a progressive storage of substrates that gradually affects lysosomal, cellular and tissue physiology. Their pathophysiological consequences vary according to the nature of the stored substrate, making LSDs complex and multisystemic diseases. Some LSDs result in near normal life expectancies, and advances in treatments mean that more people reach the age to have children, so considering the effects of LSDs on fertility and the risks associated with having children is of growing importance Objectives: As there is a lack of clinical studies describing the effect of LSDs on the physiology of reproductivity, we undertook a scoping review of studies using animal models of LSDs focusing on reproductive parameters. Methods: We searched six databases: MEDLINE, LILACS, Scopus, Web of Science, Embase and SciELO, and identified 49 articles that met our inclusion criteria. Results: The majority of the studies used male animal models, and a number reported severe morphological and physiological damage in gametes and gonads in models of sphingolipidoses. Models of other LSDs, such as mucopolysaccharidoses, presented important morphological damage. Conclusion: Many of the models found alterations in reproductive systems. Any signs of subfertility or morphological damage in animal models are important, particularly in rodents which are extremely fertile, and may have implications for individuals with LSDs. We suggest the use of more female animal models to better understand the physiopathology of the diseases, and the use of clinical case studies to further explore the risks of individuals with LSDs having children.